Enabling strategic decision-making in organizations through dataplex - Manoharan, Siva Ganapathy Subramanian; Mohapatra, Sanjay; Manoharan, S. (Subramanian); Subramaniam, Rajalakshmi (Emerald points., 2023)
Enabling Strategic Decision-Making in Organizations through Dataplexbreaks down the role of data in strategic decision making, examining the organizational benefits but also utilising real-world examples of limitations and challenges and how these can be overcome.